Harmony of Technology and Nature: A Systematic Analysis of Renewable Energy Development - Prasetya, Luhur Adi; Wibawanto, Slamet; Mahandi, Yogi Dwi (Institute Of Advanced Knowledge and Science, 2025)
The transition to renewable energy is an important step to address the energy crisis and global climate change. Renewable energy technologies, such as solar panels, wind turbines, and energy storage systems, have developed rapidly with increasing efficiency, such as the 45% efficiency of solar panels. However, key implementation challenges include dependence on weather conditions that affect the stability of energy supply as well as cost and infrastructure constraints. Fiscal incentives and carbon pricing policies have proven effective in driving renewable energy adoption, as seen in Germany and China. On the other hand, artificial intelligence (AI) and blockchain technologies are playing a role in improving energy distribution efficiency and power consumption optimization, while the renewable energy sector has created millions of jobs with a projected increase to 35 million by 2030. However, investment inequality between developed and developing countries remains a major challenge. Therefore, accelerating the green energy transition requires policies that simplify licensing procedures, support technological innovation, and encourage collaboration between the public and private sectors. This research highlights the importance of a holistic approach covering technology, policy and investment aspects to realize a more efficient, inclusive and environmentally sustainable energy system.